Prospective study on warfarin and regional chemotherapy in patients with pancreatic carcinoma - Nakchbandi, Wes; Müller, Herwart; Singer, Manfred V.; Löhr, J.-Matthias; Nakchbandi, Inaam (Journal of gastrointestinal and liver diseases, 2008)
Aims: The aim is to prospectively examine the effect of regional gemcitabine and mitomycin-C with systemic gemcitabine together with warfarin in patients with inoperable pancreatic carcinoma, and compare the effect to systemic gemcitabine alone.Methods: Seventeen patients received 1.25 mg of warfarin daily, gemcitabine 800 mg/m˛ on day 1 and mitomycin-C 8 mg/m˛ on day 2 regionally and gemcitabine 800 mg/m˛ on day 14 peripherally. The cycle was repeated every 4 weeks.Results: Median survival since presentation was 6.8 months, while median total survival was 9.6 months. Excluding the 3 patients who died before receiving any therapy, the median survival since presentation resulted in 10.7 months and the median total survival, 12.7 months. One patient developed bleeding that required transfusion and 2 patients developed anemia (Grades III/IV). Comparing these data to historical controls of large cohorts supports the notion that this regimen offers a viable alternative to systemic gemcitabine alone.Conclusion: A regimen consisting of regional gemcitabine and mitomycin-C with systemic gemcitabine and low-dose warfarin compares favorably to the gold standard of systemic gemcitabine. These data suggest the feasibility of a large prospective study on the use of warfarin and combined regional and systemic chemotherapy in patients with pancreatic carcinoma.
Keine DOI vorhanden
Gesehen am 22.03.2022